2014
DOI: 10.1158/0008-5472.can-13-3147
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the Polycomb Mark from Bivalent Promoters Leads to Activation of Cancer-Promoting Genes in Colorectal Tumors

Abstract: In colon tumors, the transcription of many genes becomes deregulated by poorly defined epigenetic mechanisms that have been studied mainly in established cell lines. In this study, we used frozen human colon tissues to analyze patterns of histone modification and DNA cytosine methylation in cancer and matched normal mucosa specimens. DNA methylation is strongly targeted to bivalent H3K4me3- and H3K27me3-associated promoters, which lose both histone marks and acquire DNA methylation. However, we found that loss… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 50 publications
(54 reference statements)
3
46
0
Order By: Relevance
“…During colorectal cancer initiation, gains and losses of the H3K4me3 modification at promoters are associated with differential gene expression (86). The loss of the H3K27me3 modification has also been linked to aberrant activation of oncogenic gene transcription, including MKI67 and CD133 , a proliferation marker and a cancer stem cell marker, respectively (87). Moreover, the loss of both H3K4me3 and H3K27me3 modifications is associated with aberrant gains in promoter methylation in colorectal cancer (87).…”
Section: Cis-regulatory Elements Are Targets Of Genetic and Epigenetimentioning
confidence: 99%
See 1 more Smart Citation
“…During colorectal cancer initiation, gains and losses of the H3K4me3 modification at promoters are associated with differential gene expression (86). The loss of the H3K27me3 modification has also been linked to aberrant activation of oncogenic gene transcription, including MKI67 and CD133 , a proliferation marker and a cancer stem cell marker, respectively (87). Moreover, the loss of both H3K4me3 and H3K27me3 modifications is associated with aberrant gains in promoter methylation in colorectal cancer (87).…”
Section: Cis-regulatory Elements Are Targets Of Genetic and Epigenetimentioning
confidence: 99%
“…The loss of the H3K27me3 modification has also been linked to aberrant activation of oncogenic gene transcription, including MKI67 and CD133 , a proliferation marker and a cancer stem cell marker, respectively (87). Moreover, the loss of both H3K4me3 and H3K27me3 modifications is associated with aberrant gains in promoter methylation in colorectal cancer (87). Apparent gains and losses of the H3K27me3 modification at promoters also discriminates androgen deprivation-resistant versus sensitive prostate cancer cells, suggesting a role for epigenetic alterations at promoters during cancer progression (88).…”
Section: Cis-regulatory Elements Are Targets Of Genetic and Epigenetimentioning
confidence: 99%
“…Unexpectedly, the majority of genes controlled by such hypermethylated bivalent promoters simultaneously showed increased expression levels in lymphoma samples. An up-regulation of genes controlled by bivalent promoters was recently shown in colorectal cancers17. However, it was reported that hypermethylation led to the continued repression of genes.…”
mentioning
confidence: 94%
“…Emerging evidence indicates that bivalency poises genes for expression and is likely a key regulatory mechanism in transdifferentiation during lineage commitment as well as in dedifferentiation during onset and progression of cancer ( Fig. 1) (20)(21)(22)(23)(24). We propose that partial recapitulation of the bivalent chromatin landscape of pluripotent cells in some cancer types-termed "oncofetal epigenetic control" in this review-can offer novel avenues for the development of specific and selective diagnostic and therapeutic approaches.…”
mentioning
confidence: 85%
“…Although there is a reduction in the number of bivalent sites in cancer through loss of H3K27me3, DNA at bivalent promoters was observed to be hyper-methylated (20,61,62), whereas in normal cells, those promoters tend to have lower levels of methylation, which is accompanied by increased gene expression (63,64). In the context of cancer, bivalency seems to be crucial for keeping cells in a differentiated state as loss of bivalent control at the developmentally regulated HOX genes plays an important role in both oncogenesis and tumor suppression (22,65).…”
Section: Bivalent Epigenetic Landscapementioning
confidence: 99%